Level of students' argumentation skills in socio-scientific issues of biodiversity subject - Santika, Ayu Ratna (Bioedunis Journal, 2024)
Argumentation is one of the important skills that students need to master in facing the global challenges of the 21st century. Argumentation plays an important role in the learning process to build students' understanding, which will also develop their critical thinking skills. Argumentation skills are not just a process of gathering facts but also involve the coordination between evidence and theory. This research aims to analyze students' argumentation skills in social-scientific issues on the of biodiversity subject. The method used in this research is the descriptive method. The subjects of the research are first-grade students at senior high schools in Subang Regency. This research uses open-ended questions to analyze the presence of students' argumentation components based on the Toulmin Argumentation Pattern: claim, data, warrant, rebuttal. The results of this study indicate that the most frequently expressed argumentation component by students in the learning of social-scientific issues on biodiversity material is the claim, placing students' argumentation skills at level 1.